Advancements in artificial intelligence, blockchain technology, and IoT in higher education : mitigating the impact of Covid-19 - Subhendu Kumar Pani (Apple Academic Press, 2024)
This new volume focuses on the application of artificial intelligence, blockchain technology, and the Internet of Things to meet the new challenges faced by higher education due to the Covid-19 pandemic, which necessitated restrictions to gathered groups of students and others and increased the need for alternative means of teaching, learning, and communication. With a need to find alternatives to the traditional face-to-face teaching and learning during the pandemic, the authors of Advancements in Artificial Intelligence, Blockchain Technology and IoT in Higher Education: Mitigating the Impact of Covid-19 discuss the best use of technologies in many areas of study in higher education. The book addresses the growing role of AI in the digital transformation in higher education systems, looking at learning and teaching models. The authors look at using digital technologies to create smart universities and the use of blockchain and IoT technologies in higher education